The scientific and practical way to choose scientific research topic and give it a title - Rebbahi, Mostafa; Khelifi, Chawki (Journal of Human Sciences, 2022)
The most difficulty, which any researcher facing with, in the scientific field, mainly for master and doctoral student , is the choice of a scientific research topic, especially since they are restricted by a specified time, for this, and to passing this delicate phase, the researcher must follows a specific steps in accordance with scientific and practical methodology that includes a set of conditions and norms that must be respected in this regard, which we are addressing in first time. But, the choice of a theme will remain meaningless, unless we put it in a framework that defines it, we mean here, to give any subject research its scientific meaning, it must make it a meaningful title that constitutes its scientific identification card, as succeeding to formulate some title means the success in the choice of scientific research topic, and consequently success in achieving the objectives that are desired by this research, the question that can only be achieved by respecting a set of the criteria and conditions when formulating the title which we are addressing in second time .